О фауне выемчатокрылых молей (Lepidoptera. Gelechiidae) отделения Михайловская целина Украинского степного заповедника - Пискунов, В.И. (Вестник зоологии, 1973)
The article deals with the data on 15 species of Gelechiidae collected in the Ukrainian steppe reservation in the division Mikhailovskaya tselina (Lebedinsky district, Sumy region). All these species are found in the reservation territory for the first time.